Fibrin Metabolism in Patients with Acute Myocardial Infarction During and After Treatment with Tissue-Type Plasminogen Activator - Ring, Michael E; Butman, Samuel M; Bruck, Denise C; Feinberg, William M; Corrigan, James J, Jr (Thrombosis and Haemostasis, 1988)
In order to define some of the determinants of successful thrombolysis and reocclusion during fibrinolytic therapy for acute myocardial infarction (AMI), specific molecular markers of fibrin metabolism were serially measured in 15 patients with AMI treated with tissue-type plasminogen activator (t-PA). Fibrin formation was assessed by measurement of fibrinopeptide A (FpA) and fibrinolysis by assay of B-P peptides 1—42 and 15—42 and crosslinked fibrin degradation products (XDP). At baseline, FpA levels were high while markers of fibrinolysis were near normal. Following a 90-minute infusion of t-PA (0.5—1.1 mg kg−1 hr−1), all markers of fibrinolysis increased. Levels of FpA remained elevated despite heparin at the initiation of cardiac catheterization. None of these markers discriminated between patients with successful reperfusion from those without. At 4 hours, B-β 15—42 peptide and XDP levels remained elevated suggesting persistence of fibrinolysis beyond the short circulatory half-life of t-PA. FpA levels at 4 hours were lower in patients who underwent acute coronary angioplasty compared to those who received additional low dose t-PA (12.3 ± 4.5 vs. 30.4 ± 5.5 ng/ ml, p <0.05). By 48 hours, markers of fibrinolysis had returned toward normal except in 2 patients with persistently elevated B-P 15—42 peptide levels who suffered reocclusion on days 5 and 6 (75 and 44 vs. 29 ± 3 nM, p <0.005). In conclusion, molecular markers of fibrin metabolism during fibrinolytic therapy may provide clinically relevant data.
Keywords: Fibrinolytic therapy; Tissue; type plasminogen activator; Acute myocardial infarction; Plasminogen activator inhibitor; Percutaneous transluminal coronary angioplasty; Fibrin metabolism